Chronic tubal pregnancy without positive pregnant tests, a rare but possible scenario - Shuo-Mei Hung; Jen-Ruei Chen (Elsevier, 2024)
Objective: Chronic ectopic pregnancy is a variant of ectopic pregnancy featured with a low or normal serum beta-human chorionic gonadotropin (β-hCG) test. Obscure clinical presentations and non-specific images make chronic ectopic pregnancy a diagnostic dilemma until now. Case Report: A 40-year-old female was misdiagnosed as tubo-ovarian abscess initially due to chronic lower abdominal pain, negative pregnancy test, and a complicated pelvic mass on abdominal CT scan and serial follow-up ultrasonography. Diagnostic laparoscopy was performed because of persistent pelvic mass with abdominal pain and irregular vaginal bleeding. Left tubal salpingectomy was performed and pathology reported a hematocele with inactive trophoblast tissue. Chronic ectopic pregnancy was proved. The symptoms resolved completely after our surgery. Conclusion: An abnormal adnexal mass with a history of recent pregnancy could still be possible for chronic ectopic pregnancy even with a negative pregnancy test. Diagnostic laparoscopy and pathology confirmation could be helpful when the clinical manifestation is confusing.